Transcatheter aortic valve implantation versus surgical aortic valve replacement in low-risk patients: a propensity score-matched analysis. (30th September 2019) - Schaefer, Andreas; Schofer, Niklas; Goßling, Alina; Seiffert, Moritz; Schirmer, Johannes; Deuschl, Florian; Schneeberger, Yvonne; Voigtländer, Lisa; Detter, Christian; Schaefer, Ulrich; Blankenberg, Stefan; Reichenspurner, Hermann; et al.
Abstract: OBJECTIVES: The aim of the study was to determine the differences in outcomes of surgical aortic valve replacement (SAVR) and transcatheter aortic valve implantation (TAVI) in low-risk patients. METHODS: All patients with a logistic EuroSCORE II <4% who underwent transfemoral TAVI between 2008 and 2016 ( n  = 955) or SAVR between 2009 and 2014 ( n  = 886) at our centre were included. One hundred and nine patients per group were available for propensity score matching. RESULTS: Mortality during the 30-day follow-up showed no differences (SAVR vs TAVI: 1.1% vs 1.8%, P  = 1.0) but the rates of permanent pacemaker implantation (0.0 vs 14.8%, P  < 0.001) and paravalvular leakage ≥ moderate (0.0 vs 7.0%, P  = 0.017) were higher in TAVI patients. No difference was found regarding postoperative effective orifice area and transvalvular pressure gradients. Although, the 1-year survival was similar between both groups; 3- and 5-year survival was significantly inferior in the TAVI patient cohort. CONCLUSIONS: TAVI yielded similar short-term outcomes compared with SAVR despite higher rates of permanent pacemaker implantation and paravalvular leakage ≥ moderate, but inferior long-term survival. Poorer long-term outcomes of the TAVI patient cohort were attributable to a more comorbid TAVI population. This emphasizes the need for long-term results from randomized controlled trials before TAVI can be broadly expanded to younger low-risk patients.